MAGNETIC BASEMENT MODELLING USING MAGB_INV PROGRAM IN TALU-TOMBANG GEOTHERMAL REGION, WEST SUMATRA - Aulia Daizar, Ariel
Subsurface structure modeling is crucial for hydrocarbon and mineral exploration activities. The presence of hydrocarbons, minerals and geothermal resources are usually found in sedimentary basins, but there are not many programs that can be used to estimate the depth and presence of sedimentary basins. The alternative is to identify the magnetic basement. Magnetic methods can be used to determine magnetic bedrock or magnetic basemnt. Basement modeling can be used for geothermal exploration which is being intensively developed in the energy industry. There have been many studies on geothermal manifestations, but not many have investigated the magnetic basement, especially in Indonesia. In this study, modeling with an anomaly inversion process in the Talu – Tombang geothermal area, West Pasaman district, West Sumatra province will be carried out using a MATLABbased program called MagB_Inv. The MagB_Inv program has been proven to be able to perform computations quickly with high precision, is able to process largescale data and can determine the three-dimensional structure of the magnetic basement. This program utilizes the Fourier transform to generate the topography of the basement surface. The data is presented with two-dimensional and threedimensional modeling of the results of a rapid iterative procedure on magnetic anomaly data, initial input parameters, frequency, and convergence criteria to produce a magnetic basement depth model. The result of the modeling is a decreased magnetic basement relief on the East side of the research region with the depth of 2 km from the earth's surface. The rock group that is thought to make up the magnetic basement is a group of Pre-Tertiary rocks, namely Metamorphic rocks composed of Quartzite and Gneiss rocks.